Relative abundance of oribatid mites (Sarcoptiformes: Oribatida) in two tillage systems of irrigated and rain-fed wheat farms of Khodabandeh County, Iran - Mahshid Mirzaei-Pashami; Alireza Saboori; Jamasb Nozari; Kamran Afsahi (Persian Journal of Acarology)
Biodiversity is an important factor in soil quality and functionality. Physical and chemical changes during agricultural operations influence on soil biodiversity. Tillage and irrigation significantly change the life of soil microorganisms. The current study was conducted in Khodabandeh County during the wheat growing season. The effect of the first treatment (two tillage systems: conventional and no-tillage systems) and the second treatment (months) in two years on the biodiversity of oribatid mites, were investigated in irrigated and rain-fed wheat farms. Twelve samples were collected randomly per each sampling time during 21 April, 5 June and 30 July 2014 and 10 May, 12 June and 31 July 2015 coinciding with tillering stage, stem elongation and harvesting. Twelve species from eight families and 12 genera were identified. Among them, Opiella nova with 24.4% relative abundance was the abundant species in 2014 and Rhinopia bipectinata with 27.5% was the abundant species in 2015. The highest value of the Shannon-Wiener diversity index was observed in the irrigated no-tillage (I-NT) system. The statistical results of the ANOVA test showed a significant difference in the Shannon-Wiener diversity index among the four systems. Shannon-Wiener diversity index in the I-NT system had a significant difference with the I-CT system (irrigated-conventional tillage). There were no significant differences between I-CT and I-NT in terms of species richness index while differences between I-NT and R-CT systems and between R-NT and R-CT systems were significant. Also, results showed that species richness index at the time of tillering stage was significantly higher than that of stem elongation. The interaction between two treatments did not show a significant difference. There was no significant difference between the two years, so the results of the two years were merged.